Role of topical intranasal steroids in pediatric hearing loss due to otitis media with effusion: the experiences - Swain, Santosh Kumar; Behera, Ishwar Chandra; Agrawala, Rohit; Shajahan, Nibi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Otitis media with effusion (OME) is one of the commonest diseases causing hearing impairment in children. Hearing loss in early childhood may lead to risk of speech and language problems and psychosocial abnormalities. Aim of this study is to evaluate the role of topical intranasal steroids (Mometasone furoate) in pediatric hearing loss due to otitis media with adenoid hypertrophy. Methods: A prospective study carried out at a tertiary care teaching hospital of eastern India where 104 children participated with diagnosis of otitis media with effusion and hearing loss between 2017 to 2019. These participants were divided into study group and control group. The age group of the children was between 5 to 10 years. Detail otoscopic examination, pure tone audiometry, tympanometry and nasopharyngeal endoscopy were done for assessing the hearing loss, fluid in the middle ear and adenoid hypertrophy. Results: There is improvement of hearing in the study group as compared to control group. A significant improvement in hearing was seen in the study group (p=0.0001). In the study group, 37 (77.08%) out of the 48 children OME resolved over a period of 12 weeks after treatment in comparison to 18 (37.50%) in the control group (p=0.0004). Conclusions: Intranasal topical steroids can be a treatment option alternative to surgery in OME. As it is short term follow up in this study, long term follow up is required. Intranasal mometasone furoate treatment can be considered as a good treatment option for OME.